No Value of Routine Brain Computed Tomography 6 Weeks after Evacuation of Chronic Subdural Hematoma - Pedersen, Christian Bonde; Sundbye, Filippa; Poulsen, Frantz Rom (The Surgery Journal, 2017)
Background The aim of this study was to evaluate the value of planned control postoperative brain computed tomography (CT) scan performed 4 to 6 weeks after the evacuation of chronic subdural hematoma.Materials and Methods This retrospective study examined 202 patients who during a 2-year period from 2011 and 2012 underwent surgical treatment for chronic subdural hematoma (CSDH). Information on patient age, sex, alcohol consumption, anticoagulant/antiplatelet treatment, history of head trauma, Glasgow coma scale (GCS), neurological symptoms, laterality of CSDH, and surgical technique was retrieved from patient charts.Results Overall, 27 out of 202 patients had a recurrence of CSDH and re-evacuation of the hematoma was performed. In all patients recurrence of neurological symptoms preceded the planned postoperative control brain CT 4 to 6 weeks after primary surgery.Conclusion Routinely postoperative control brain CT scan 4 to 6 weeks after the evacuation of a CSDH has no clinical value.
Keywords: chronic subdural hematoma; postoperative CT scan; evacuation; recurrence